Diagnosis of Student Character Education Through the Contribution of Principal Interpersonal Communication and Teacher Performance - Hanafiah Hanafiah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to investigate the principal's interpersonal communication and teachers' performance, the relationship of the principal's interpersonal communication to students' character education, the relationship of teachers' performance to students' character education, and the mutual relationship between the principal's interpersonal communication and teachers' performance on character education of high school students in Langsa. This study utilized a quantitative approach, using a cross-sectional survey method. The population and samples in this study were five senior high schools in Langsa. This study found that three principals scored 56.83%, meaning that the principal possessed good interpersonal communication, and two principals scored 43.17%, implying that the principal had excellent interpersonal communication. Furthermore, 35 of 92 teachers scored 38.04% in the good category, and 57 teachers scored 61.96% in the excellent category. Then, the partial test results obtained a relationship between the principal's interpersonal communication on students' character education (0.041), and there was a relationship between teachers' performance and students' character education (0.029). Furthermore, simultaneous test results obtained that there was a jointly significant relationship between the principal's interpersonal communication and teacher's performance on students' character education (0.01), where X1 variable (Principal interpersonal communication) and X2 variable (Teacher performance) influenced for 58.8% on Y variable (students' character education). In comparison, other variables influenced 41.2% of high school students’ character education in Langsa.